The effectiveness of cover crops on soil loss control in Gede catchment of Malang Regency, Indonesia - Nurul Muddarisna; Eny Dyah Yuniwati; Heni Masruroh; Aulia Rahman Oktaviansyah (Journal of Degraded and Mining Lands Management, 2021)
Cover crop is an important factor which affects soil loss. The lost of soil potential is affected by plant morphology. The aim of this study was to elaborate on the effectiveness of the type of cover crops to soil loss in the same morphology and characteristic of soil. The study was carried out by applying erosion plots. Soil loss measurements were conducted four times in each demonstration plot. Soil loss for each plot was analyzed in the laboratory. The result showed that the most erodible soil with the highest amount of soil loss was in the pre onion plot and the most effectiveness for soil loss control was carrot plot. The amounts of soil loss for carrot, cabbage, and pre-onion were 0.040991 kg/8 x 10-4ha, 0.069901 kg/8 x 10-4ha, and 0.077800 kg/8 x 10-4ha, respectively. The highest runoff of 60.554 L/8 x 10-4ha,  was observed at the pre onion plot. Based on the result, the most effective cover crop for soil control was the carrot. The important parts of cover crops which influenced soil loss were the shape of shade leaves and type of roots.